Кинетическая специфика инспиративного дискурса харизматических политиков современной Германии - Петлюченко, Н. В.; Петлюченко, Наталія Володимирівна; Petlyuchenko, N. V.; Petlyuchenko, Nataliya V. (Одеса, 2017)
У статті представлено результати дослідження кінетичного компонента інспіративного дискурсу сучасних німецьких політиків (Віллі Брандт, Йошка Фішер, Герхард Шредер, Йоахим Гаук), які в Німеччині є загальновизнаними харизма¬тиками. Аналізуються синхронні і асинхронні мовленнєвосупровідні жести правої руки відносно просодичної емфази в інспиративних зверненнях німецьких політиків до публіки.

This article focuses on the kinetic component in the inspiring discourse of contemporary German politicians (Willy Brandt, Joschka Fischer, Gerhard Schröder, Joachim Gauck) generally recognized as 'charismatic personalities'. We will dwell on the analysis of synchronous and asynchronous right hand co-speech gestures in relation to prosodic emphasis in inspiring public speeches of German politicians.
Петлюченко Н. В. Кинетическая специфика инспиративного дискурса харизматических политиков современной Германии / Н. В. Петлюченко // Одеський лінгвістичний вісник.– 2017. – Вип. 9. – Т.1. – С. 195-200.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Research Subject Categories::HUMANITIES and RELIGION; інспіративний дискурс; харизматик; мовленнєвосупровідний жест правої руки; синхронний; асинхронний; просодична емфаза; inspiring discourse; charismatic; right hand co-speech gesture; synchronous; asynchronous; prosodic emphasis